2013
DOI: 10.5588/ijtld.12.0286
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance in new tuberculosis patients: burden and implications [Short communication]

Abstract: In 2010, 30 countries with anti-tuberculosis drug resistance surveillance data were each estimated to have more than 700 multidrug-resistant tuberculosis (MDR-TB) cases among their notified TB cases. New TB patients comprised a median of 54% (interquartile range 45-67) of the MDR-TB cases. The occurrence of MDR-TB in a new TB patient is a warning sign that MDR-TB is spreading in a community. While MDR-TB case-finding efforts should first prioritize previously treated patients, reaching universal access require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…In Moldova, for which adequate surveillance data are available, 23.7% of new TB cases involve an MDR strain ( 3 ). A recent report of surveillance data in countries with >700 estimated MDR TB cases per year indicated that more than half of the reported pulmonary MDR TB cases were new cases ( 20 ). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Moldova, for which adequate surveillance data are available, 23.7% of new TB cases involve an MDR strain ( 3 ). A recent report of surveillance data in countries with >700 estimated MDR TB cases per year indicated that more than half of the reported pulmonary MDR TB cases were new cases ( 20 ). …”
Section: Discussionmentioning
confidence: 99%
“…Although previous treatment for TB and contact with persons infected with drug-resistant strains have been reported as strong risk factors for MDR TB, the role of HIV infection, young age, sex, and previous imprisonment are less clear ( 12 , 28 ). The high proportion of new cases and the lack of association of other traditional risk factors with drug-resistant TB suggest an increased role of ongoing transmission in the community outside established risk groups for becoming infected with drug-resistant strains of M. tuberculosis ( 19 , 20 , 29 ). …”
Section: Discussionmentioning
confidence: 99%
“…This is expected to increase the patient coverage of DST in Uzbekistan, including the previously untreated TB patients who, as in many other countries, harbour a substantial part of the MDR-TB caseload [34]. If coupled with an efficient electronic system of data capture this would also enable the use of data from routine diagnostic testing for drug resistance surveillance in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…In absolute numbers, the majority of cases is observed in new patients, who never received a treatment before and who were contaminated by a patients harbouring a resistant strain. 13 As a consequence, in some regions of the world, new patients are at high risk of having MDR-TB even in the absence of previous treatment.…”
Section: Risk Factors For Mdr-tbmentioning
confidence: 99%